The response time of the magnetopause reconnection location to changes in the solar wind: MMS case study - K. J. Trattner; J. L. Burch; R. Ergun; S. A. Fuselier; R. G. Gomez; E. W. Grimes; W. S. Lewis; B. Mauk; S. M. Petrinec; C. J. Pollock; T. D. Phan; S. K. Vines; et al. (Geophysical Research Letters)
Abstract Reconnection at the Earth's magnetopause is the mechanism by which magnetic fields in different regions change topology to create open magnetic field lines that allow energy, mass, and momentum to flow into the magnetosphere. It is the primary science goal of the recently launched MMS mission to unlock the mechanism of magnetic reconnection with a novel suite of plasma and field instruments. This study investigates several magnetopause crossings in the vicinity of the X‐line on 19 September 2015 and compares the observed X‐line location with predictions from the Maximum Magnetic Shear model. Rotations of the interplanetary magnetic field (IMF) during the magnetopause crossings together with the close proximity of the four MMS satellites are used to determine the response time of the reconnection X‐line location to changes in the IMF. The reconnection location exhibits a continuous motion during slow changes in the IMF but a delayed response to sudden changes in the IMF.